Op zoek naar verbindingen tussen school en thuis: Over de strategieën die moslimkinderen op school en thuis hanteren - Juchtmans, Goedroen (Religie & Samenleving, 2015)
This paper focuses on how Muslim children (10-11 years), attending three Flemish schools, move between their home and school culture and how they deal with competing religious expectations from both worlds or with contrasts between own wishes and actual possibilities. In dealing with these issues, it is assumed that children act as social actors capable of adopting creative strategies, but that this agency is located and may sometimes be restricted by adults. This paper argues that children, if possible, choose for positive, connecting strategies. However, in situations wherein adults at school and at home deploy their power status, by problematizing religious differences or by enforcing children to an univocal religious choice, these strategies come under pressure, resulting in more ambivalent or more problematic strategies.